Ideologi Ekonomi Politik Media RCTI Dan TV ONE Dalam Mengambil Angle Pemberitaan Menjelang Pemilu 2014 - Murfianti, Fitri; Nugroho, Cahyo (Capture : Jurnal Seni Media Rekam, 2015)
In the democratic state like Indonesia, election is a routine agenda as a democratic party, which was held every five years. The democratic partyis now enlivened by the presence of party cadres who are also involved in the media world. The party cadres use the media because they know that there is a great impact caused from it. They can determine the direction of the news according to their political ideology. The research has the aim to know the strength of the ideology preaching of candidate which is also engaged in the world of media, namely, Harry Tanoesoedibjo and Abu Rizal Bakrie, through media impressions in its program.The study used a qualitative research and focused on the news program Seputar Indonesia Pagi RCTI and Kabar Pagi TV One. The collecting data used observation, literature, and documentationtechniques which took on April 2-6th, 2014. The data analysis applied the Framing techniques byGamson and Modigliani.The result showed that the news program Seputar Indonesia Pagi RCTI andKabar Pagi TV One constructed their own interests, which aims to improve imaging in the eyes of the audience which resulted in an increase in the vote at election time.Keywords: framing, angle, and news